Use and design considerations of sprinkler systems in Colorado - Code, W. E., author; Colorado A&M Experiment Station, publisher (Colorado State University. Libraries, 1952)
Sprinkling can be used advantageously in Colorado to irrigate rough or uneven lands where surface irrigation would be difficult or unsatisfactory. It is useful on lands that cannot be properly prepared for irrigation because of thin top soils underlain by gravel or hardpan. Most of the hazards of erosion on many of our steep slopes are avoided by sprinkling. A better cover crop can be grown in orchards and root injury by furrowing out tools is eliminated. Light irrigations can be effectively applied by sprinkling and, especially on light textured soil, a considerable saving of water is possible. Sprinkling offers a very valuable alternative method of applying water but its greatest economic value probably lies in the development of new lands. The high capital cost of equipment can about equal the cost of preparing land for surface irrigation in many cases. Practically no land preparation is necessary under sprinkling. Cost of power is of sufficient importance that it should be given serious consideration in making a choice. The design of a sprinkler system should not be attempted by the inexperienced. It is an engineering problem in which the engineer should have a knowledge of soils and plants.
CER47-52WEC39.
May 2, 1952.
Keywords: Sprinkler irrigation -- Colorado